La regulación de las criptomonedas frente a los principios tributarios de generalidad y equidad”. - Garcia Peña, Bryan Álvaro (2020)
The present thesis entitled: "THE REGULATION OF CRYPTOCURRENCY AGAINST THE TAX PRINCIPLES OF GENERALITY AND EQUITY"; It is the result of the study of a problem that negatively affects the State, as the principles of generality and equity are not considered, compared to the regulation of cryptocurrencies, as a digital means of exchange, when the purchase and sale of the same over the internet is recognized , but not to identify it as a tax burden, being necessary to contribute with the State, therefore with public spending, contributing with taxes, including the income tax and the tax on the outflow of foreign currency. Situation that violates the provisions of article 300 of the Constitution of the Republic of Ecuador, which clearly establishes that taxes are applied to the generality of people, with equal rights and without any discrimination, in addition to that, the tax on the Income regulated in article 2 of the Tax Regime Law, is made up of income from Ecuadorian source obtained free of charge or for consideration from work, capital, or both sources, consisting of money, species or services and income obtained in abroad by natural persons domiciled in the country or national companies. Postulates that served as the basis to raise the need for reform, including within the tax regulations, provisions that regulate the transaction, holding and investments of cryptocurrencies, as a generator of income tax and tax on the outflow of foreign currency, considering this trade as a tax burden, which would benefit all Ecuadorians.